With confidence comes success: an exploration of high school students’ mental health education from the perspective of self-efficacy theory - Su, Peng; Li, Xiaolong (Frontiers in Psychology, 2026)
IntroductionHigh school is a critical developmental period in which adolescents’ psychological functioning and social adaptability are rapidly reconfigured. However, mental health education in Chinese senior high schools often lacks systematic approaches in preventive intervention, pedagogical depth, and the cultivation of students’ psychological potential. Self-efficacy theory offers an informative lens for improving school-based mental health education.MethodsSituated in the context of senior high school mental health education, this qualitative study used semi-structured interviews and grounded theory to examine how self-efficacy is generated and evolves across learning and everyday-life contexts, and how it relates to mental health outcomes. Participants were recruited from a senior high school in Zhengzhou. Twenty-three students in Grades 10–11 were interviewed. Data were analyzed using an iterative grounded-theory coding procedure to develop core categories and an integrative relational model.ResultsThe findings indicate a close and dynamic association between self-efficacy and adolescents’ mental health. Success and failure experiences, as well as feedback in key situations—such as academic stress, peer interactions, and self-evaluation—shape both moment-to-moment fluctuations and the longer-term development of self-efficacy. These self-efficacy processes are linked to emotional stability, coping patterns, and overall psychological adjustment.DiscussionWe propose a self-efficacy–oriented mechanism for mental health education and outline a coordinated support pathway spanning school and family. The findings provide theory-grounded and actionable implications for shifting school mental health work from predominantly reactive remediation toward development-oriented prevention, and for strengthening systematic home–school collaboration in practice.